Aspects of Considering the Phenomenon of Connotation: Lacunarity and Emotional Valency - N. N. Kislitsyna; S. G. Agapova (Научный диалог, 2020)
The features of the connotation phenomenon in the aspect of the theory of lacunarity and the concept of emotional valency are considered. The result of the analysis of synchronized databases of reference information systems “Scientific electronic library of Theses and Dissertations”, “Electronic library of dissertations”, “Man and science” and “Library of dissertations” for the study of the connotation phenomenon is presented. A dissertation catalog has been compiled, including 184 works in which the subject, object or separate issue under consideration is connotation, a graphical explication of the results of the content analysis of these dissertations is presented, and the analytical and prognostic potential of the developed linear graphs is described. Extensional and intensional directions of the study of connotation, as well as their fluctuations, are shown. The source of illustrative material was the parallel sub-corpus (English) of the National Corps of the Russian Language. The question of the relationship of the emotional coloring of the word and emotional connotation is considered. It is stated that the study of connotation as a multidimensional phenomenon requires an integrative approach and the convergence of humanitarian and natural sciences. It is concluded that the use of the theory of lacunarity with respect to the study of the connotation of linguistic units seems promising, allowing to systematize the concept of the phenomenon of connotation in the framework of modern linguistics.